Spiritual Distress and Spiritual Needs of Chronically Ill Patients in Poland: A Cross-Sectional Study - Maciej Klimasiński (International Journal of Environmental Research and Public Health, 2022)
Introduction: Spiritual care is needed in a clinical setting to improve the patients’ quality of life. Deep connection with another person and delight with the beauty of nature or art and (in some cases) with God are all transcendental experiences. They may enable patients to ascribe meaning to their life with a chronic illness, find hope and well-being despite burdening symptoms. The opposite situation: lack of inner peace, inability to accept what is happening, feeling disconnected from others is called spiritual distress. Objectives: The aim of this research is to assess spiritual distress and spiritual needs of a group of Polish chronically ill patients and find associations with independent variables in order to provide data for recommendations on spiritual care in Poland. Patients and methods: 204 patients treated at the University Hospital and the Cystic Fibrosis Clinic in Poznan were surveyed in 2017 and 2018 with an original questionnaire. Results: Over half of the patients felt that their illness was life-threatening. A little more than half reported that faith was a resource to cope with suffering. Almost all patients showed signs of spiritual distress, and more than half expressed spiritual needs. The intensity of distress correlated only with the severity of the disease. The most important predictor of having spiritual needs was recognizing faith as a resource. Conclusions: Spiritual needs are associated with personal beliefs; however, spirituality spans beyond the religious context since spiritual distress is unrelated to the level of religious devotion. Therefore, any patient with a severe chronic disease needs basic spiritual care, which includes being treated with compassion.